2015
DOI: 10.1136/vetreco-2015-000150
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the morphology of mammalian chordae tendineae of the mitral and tricuspid valves

Abstract: It is assumed that the human heart is almost identical to domestic mammalian species, but with limited literature to support this. One such area that has been underinvestigated is that of the subvalvular apparatus level. The authors set out to examine the morphology of the subvalvular apparatus of the mammalian atrioventricular valves through gross dissection and microscopic analysis in a small-scale pilot study. The authors examined the chordae tendineae of the mitral and tricuspid valves in sheep, pig and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The right ventricle of the goat had numerous chordae tendinae than the left ventricle. This finding was in agreement in horses [18], pigs, sheep, cows [19], and goats [34].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The right ventricle of the goat had numerous chordae tendinae than the left ventricle. This finding was in agreement in horses [18], pigs, sheep, cows [19], and goats [34].…”
Section: Discussionsupporting
confidence: 84%
“…The right ventricle had a greater number of chordae tendinae than the left ventricle in the horse [18] and pigs, sheep, and cow [19].…”
Section: Introductionmentioning
confidence: 95%
“…The fact that the RAV had a greater mean number of tendinous cords than the LAV confirmed the data previously reported for the horse by Ghoshal, 3 and for the pig, sheep and cow by Hutchison and Rea. 49 Based on these reports, however, it appears that the sheep, pig and cow, with 23, 24 and 25 for the RAV and 15, 20 and 17 cords for the LAV, respectively, 49 have a greater mean number of tendinous cords for both atrioventricular valves when compared with the horse. In addition, the number of tendinous cords was not influenced by the number of accessory leaflets, confirming what Alves et al 29 reported for the dog.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine hearts are commonly used in cardiac studies due to their similarities with the human heart at a larger scale. 47 The dissection of each heart was performed following the procedure used by Lodder et al, 48 thus to have a better visualization of the left ventricle. First, the right chambers of the heart were taken out, as well as the left atrium.…”
Section: Materials Preparationmentioning
confidence: 99%